Fermentation and aerobic stability of rehydrated corn grain silage treated with different doses of Lactobacillus buchneri or a combination of Lactobacillus plantarum and Pediococcus acidilactici - da Silva, N. C. [UNESP]; Nascimento, C. F. [UNESP]; Nascimento, F. A. [UNESP]; de Resende, F. D. [UNESP]; Daniel, J. L.P.; Siqueira, G. R. [UNESP] (American Dairy Science Association, 2018)
We investigated the effects of different types and doses of inoculants for ensiling rehydrated corn grain. Shelled corn was finely ground and rehydrated to 35% moisture. Treatments were as follows: (1) control (no additives); (2) Lactobacillus plantarum and Pediococcus acidilactici (LPPA) at a theoretical application rate of 1 × 105 cfu/g; (3) LPPA at 5 × 105 cfu/g; (4) LPPA at 1 × 106 cfu/g; (5) Lactobacillus buchneri (LB) at 1 × 105 cfu/g; (6) LB at 5 × 105 cfu/g; and (7) LB at 1 × 106 cfu/g. We detected no effect of inoculant dose. Gas losses were greater in silages treated with LB compared with control and LPPA silages. Treating silages with LB reduced the concentrations of lactic acid and ethanol and increased silage pH and concentrations of acetic acid, propionic acid, and 1,2-propanediol. At silo opening, silages treated with LB had higher counts of lactic acid bacteria but lower yeast counts than the control silage. Aerobic stability was greater for silages treated with LB and lower for silages treated with LPPA compared with the control. The LB reduced dry matter (DM) losses during aerobic exposure, whereas LPPA increased them. Prolamin content was lower in silages treated with LB compared with the control, resulting in greater ruminal in situ DM degradability. Inoculating LB to a dose of 1 × 105 cfu/g increased aerobic stability and ruminal in situ DM degradability of rehydrated corn grain silage. The addition of LPPA did not alter the fermentation process and worsened the aerobic stability of rehydrated corn grain silage. Further studies are warranted to confirm these conclusions in other corn hybrids, inoculants, and their combinations.
Keywords: corn grain; fermentation end-product; prolamin; ruminal in situ DM degradability